Antibiotic Resistance in Aquaculture and Scope of Probiotic Approach: A Review: Antibiotic Resistance and Probiotic Approach in Aquaculture - Marufatuzzahan, Marufatuzzahan; Arkh, K J Habib; Sen, Pallab; Chowdhury, Md Burhan Uddin; Nisha, Nawshin-E-Ara; Afrin, Dilruba (Journal of the Sylhet Agricultural University, 2025)
Antibiotic resistance has become a critical challenge in the aquaculture industry. Besides devastating economic losses, the alarming rate of antibiotic resistance poses a significant threat and is not limited to aquatic organisms but also affects human and other animal health through environmental and food chain transmission. Aquatic microorganisms can acquire resistance via horizontal gene transfer or evolve different mechanisms (i.e., efflux and biofilm production) to counteract the antibiotic effects. The overuse and misuse of antibiotics in aquaculture accelerate this process and promote the emergence of multidrug-resistant bacteria. To combat this growing concern, alternative strategies such as phage therapy, immunostimulants, and probiotics are being explored. Among these, probiotics represent a promising and sustainable option. These probiotic microorganisms, when administered in adequate amounts, can confer health benefits to the host, like enhancing growth and stress tolerance, improving feed utilization, and boosting the immune system. Besides disease prevention, probiotics can improve water quality by breaking down organic matter and reducing ammonia levels, thereby fostering a healthier rearing environment for aquaculture. Therefore, it can lead to a significant reduction in antibiotic use. The strategic integration of probiotics into aquaculture practices represents a promising approach to addressing antibiotic resistance and a crucial step toward sustainable and eco-friendly fish farming J. Sylhet Agril. Univ. 12(1): 116-131, 2025